EVALUASI KUALITAS LAYANAN PENDIDIKAN PADA STAIN PEKALONGAN DENGAN INSTRUMEN SERVQUAL - Ahmad Rosyid; Agus Fakhrina; Iwan Zaenul Fuad (JURNAL PENELITIAN, 2012)
This study aimed to examine the quality of academic services at STAIN Pekalongan by comparing the studentsí expectations with their perceptions of the academic services they received. SERVQUAL instrument was used to measure quality dimensions which have five aspects namely reliability, responsiveness, assurance, empathy and tangibles. The result was a gap between expectations and perceptions. Then, it was tested whether this gap was significant or not by using the Wilcoxon Signed Rank test. The next step in order to produce useful analysis for decision makers by using Important Performance Analysis (IPA). Test results showed that either all items or dimensions have a negative gap. This means that the academic services quality at STAIN Pekalongan still need some improvements.